Data Compression and Threshold Condition in Two Dimensional Static Modulation of Fourier Transform - Yong Cho, Ju; Gyu Park, Hyeon; Seok Ji, Min; Kweon Jang, Won (Asian Journal of Chemistry, 2014)
The effect of the data compression ratio and threshold condition for the data processing was discussed in the two dimensional Fourier transform technology for static modulation. We investigated the optimized threshold leveling for the improvement of signal to noise ratio and the effective data compression for the fast transmission of collected information. Static modulation to get the interferogram was discussed instead of dynamic modulation in the conventional Fourier transform spectrometers. The data compression and inverse Fourier transformed data were also discussed for fast data processing and transfer.